1998
DOI: 10.1046/j.1365-2370.1998.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA antigens and haplotypes in IgA‐deficient Brazilian paediatric patients

Abstract: In the present study we determined the HLA-A, B and DR antigenic and haplotypic frequencies in unrelated Brazilian Caucasian paediatric patients with IgA deficiency (IgA-D). Out of 17 IgA-D subjects typed for HLA A and B specificities, 12 (71%) presented B8 and/or B14; of 15 patients also typed for HLA-DR specificities, 14 (93%) were positive for at least one of the HLA markers previously reported to be associated with IgA-D, i.e. B8, B14, DR1, DR3 or DR7. The haplotypes B8, DR3, B14, DR1 and B13, DR7 were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The absence of secretory IgA in the mucosal surfaces compromises mucosal integrity, thus allowing for unhindered passage of environmental antigens into the systemic circulation, and these dietary proteins may result in cross-reactions with self-antigens. Antibodies against cow's milk, among other autoantibodies, have Besides the above-mentioned immune mechanisms, it has been postulated that homozygosity for certain haplotypes of the major histocompatibility complex genes could be a risk factor for the development of some autoimmune diseases in patients with sIgAD, with some studies showing a higher frequency of certain MHC haplotypes in individuals with sIgAD and their families (36,37). Recently, the possibility of a link between some non-HLA candidate genes and sIgAD has been reported (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of secretory IgA in the mucosal surfaces compromises mucosal integrity, thus allowing for unhindered passage of environmental antigens into the systemic circulation, and these dietary proteins may result in cross-reactions with self-antigens. Antibodies against cow's milk, among other autoantibodies, have Besides the above-mentioned immune mechanisms, it has been postulated that homozygosity for certain haplotypes of the major histocompatibility complex genes could be a risk factor for the development of some autoimmune diseases in patients with sIgAD, with some studies showing a higher frequency of certain MHC haplotypes in individuals with sIgAD and their families (36,37). Recently, the possibility of a link between some non-HLA candidate genes and sIgAD has been reported (38).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the above-mentioned immune mechanisms, it has been postulated that homozygosity for certain haplotypes of the major histocompatibility complex genes could be a risk factor for the development of some autoimmune diseases in patients with sIgAD, with some studies showing a higher frequency of certain MHC haplotypes in individuals with sIgAD and their families (36,37). Recently, the possibility of a link between some non-HLA candidate genes and sIgAD has been reported (38).…”
Section: Discussionmentioning
confidence: 99%
“…6,7 No primary genetic factor has been identified and variation in familial inheritance patterns suggests that IgAD may be due to multiple genetic defects. Several studies have shown association of HLA alleles with IgAD, [8][9][10][11] and the extended haplotype HLA-A1-B8-DR3 occurs more frequently in individuals with IgAD than it does in the general population. This haplotype is known as an autoimmunity risk haplotype as it is associated with several autoimmune pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, as described above, the HLA 8.1 haplotype is commonly related to different autoimmune diseases (i.e. type 1 diabetes and rheumatoid arthritis) and SIgAD ( 112 – 116 , 131 , 132 ). Also, both SIgAD and autoimmune disorders show familial clustering ( 58 , 131 , 133 ) and therefore, the increased frequency in autoimmune disorders might suggest a possible common genetic component in SIgAD and autoimmunity.…”
Section: Different Clinical Manifestations Of Sigadmentioning
confidence: 99%